2016
DOI: 10.1259/bjr.20150938
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of18F-fludeoxyglucose positron emission tomography/CT using point spread function reconstruction for nodal staging of colorectal cancer

Abstract: F-FDG-PET/CT reconstruction technique for improving spatial resolution and signalto-noise ratios, point spread function (PSF), has become available. We assessed the effect of PSF reconstruction on standardized uptake values and its diagnostic accuracy for lymph node staging in patients with colorectal cancer. Methods: We retrospectively analysed records from patients with colorectal cancer who underwent 18 F-FDG-PET/CT for pre-operative staging. All positron emission tomography CT (PET/CT) examinations were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The increased L/B ratio can lead to the higher detectability of lymph node metastasis. This result was mostly an accordance with previous reports that examined PSF reconstruction for evaluating lymph node metastasis in malignancies including lung cancer [ 15 , 16 ], breast cancer [ 17 ], and colorectal cancer [ 27 ]. However, the sensitivity improvement was relatively smaller than that in the lung and breast cancer studies.…”
Section: Discussionsupporting
confidence: 92%
“…The increased L/B ratio can lead to the higher detectability of lymph node metastasis. This result was mostly an accordance with previous reports that examined PSF reconstruction for evaluating lymph node metastasis in malignancies including lung cancer [ 15 , 16 ], breast cancer [ 17 ], and colorectal cancer [ 27 ]. However, the sensitivity improvement was relatively smaller than that in the lung and breast cancer studies.…”
Section: Discussionsupporting
confidence: 92%
“…With visual image interpretation, PSF reconstruction tended to increase accuracy of nodal staging in NSCLC, breast, and colorectal cancer (not statistically significant) compared to non-PSF reconstruction (from 76%, 76%, and 89% to 84%, 80%, and 92%, respectively) [ 28 , 30 , 34 ]. Another study found no significant difference in lung cancer (several types) overall staging accuracy between non-PSF and PSF reconstruction [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding visual nodal staging, PSF reconstruction did not significantly alter accuracy, but tended to increase sensitivity in lung, breast, and colorectal cancer (Table 2 ) [ 28 , 30 , 34 ]. This may be attributed to improved qualitative reads, improved (small) lesion detection, and higher diagnostic confidence [ 28 , 30 , 34 ]. Therefore, it may be worthwhile to validate these higher-resolution reconstruction algorithms for use in clinical practice, especially for detection of small lymph node metastases and lesions embedded in high background activity such as in the liver or mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…PSF modelling within tomographic reconstruction improves both spatial resolution and contrast recovery and reduces spatial noise, resulting in improved lesion detectability [2]. There is little room to question the fact that reconstruction algorithms including PSF modelling, alone or in combination with timeof-flight (ToF) capability, improve lesion detection: several studies have shown improvement in the diagnostic performance of 18 F-FDG PET/CT in various cancers [3][4][5][6][7], especially for small cancer lesions. These studies also reported a significant increase in SUV metrics [8][9][10] and here lies the controversy on PSF modelling: the risk to produce artefacts, namely edge overshoot effect sometimes referred to as the Gibbs artefact, compromising the accuracy of quantitation in small lesions [11].…”
Section: Advanced Reconstruction Algorithms: Guilty Until Proven Otherwise Versus Presumption Of Innocencementioning
confidence: 99%